The Relationship between Google Translate Use, Students’ Writing Accuracy, and Descriptive Text Quality among EFL Learners - Arifah, Tanalina; Wijayatiningsih, Testiana Deni (Jurnal Bahasa Inggris, 2025)
This study investigates the relationship between Google Translate (GT) use, students’ writing accuracy, and the overall quality of descriptive texts among EFL learners. Given that descriptive writing requires precise vocabulary, sensory details, and clear spatial organization, many students struggle with lexical selection, grammatical accuracy, and idea organization. As a result, an increasing number of learners rely on GT as a digital support tool. The purpose of this study was to synthesize existing empirical evidence and identify quantitative patterns regarding how GT influences descriptive writing performance. Employing a quantitative descriptive literature review, this study followed a PRISMA inspired procedure, screening 147 articles from Google Scholar, DOAJ, ERIC, ResearchGate, and SINTA, with 27 empirical studies meeting the inclusion criteria. Data were extracted using a structured matrix focusing on accuracy levels, error types, syntactic complexity, vocabulary use, and descriptive quality indicators. The findings revealed three major trends. First, GT had become a prominent linguistic and affective scaffold that helped students to overcome lexical and syntactic limitations, reducing anxiety and supporting idea generation. Second, GT positively influenced grammatical accuracy, lexical precision, syntactic complexity, and text organization by reducing cognitive load and enabling learners to focus on descriptive elaboration. Third, limitations persisted particularly regarding idiomatic expressions, contextual appropriateness, stylistic nuance, and expressive detail, which may hinder independent writing development when overused. The study concluded that GT is most effective as a complementary scaffold within guided instruction rather than a standalone writing tool.